Health Preservation and Environmental Protection in the Light of Prophetic Teachings - Dr. Qazi Abdul Manan; Dr. Zafar Hussain (Journal of Religion and Society, 2025)
Islam is an all-inclusive religion. It is the leader in all spheres of life. It also puts proper direction as well as instructions on health.Islam has offered all round instructions to man in order to keep his health safe and healthy. Technically, the word "environment" is an Arabic word. It refers to the surrounding environment. The term pollution is used 25 times in the Quran, which means the substances flowing to earth, water, and atmosphere, and cause harm to the human health, animals, and plants. Islam, the religion that has taught the significance of environmental pollution 1400 years ago, has gone in great lengths to conserve the environment against water, air, land, and noise pollutants to ensure that no society pollutes the environment. Through the Muslim Shariah, the Zareen principle attempts to deal with problems of human life such as climate change. It proposes the idea of planting of trees and vegetation to fight environmental pollution. The tree herbs are treated in medicine and even the old people treat themselves with them since they do not harm and are beneficial. KEYWORDS: Islamic Principles, Quran and Human Life, Pollution, Environmental pollution, Herbs and Its benefits.